Age and sequence of eruption of permanent teeth in children and adolescents in North-eastern Malaysia - Abdullah, Nizam; Mokhtar, Norehan; Naing, Lin (2003)
The aim of this study is to determine the age and sequence of eruption of permanent teeth as well as gender differences in children and adolescents in the state of Kelantan, north-eastern Malaysia. Cross-sectional data on permanent tooth eruption were collected by examining pre-school, primary and secondary school children of 5-17 years of age. The subjects were drawn by multistage random sampling from the school register. There were 2382 subjects in the sample, 1062 boys and 1320 girls. A tooth was considered erupted if any part of its crown was visible in the mouth. The data were subjected to probit analysis to compute the eruption time of each individual tooth in terms of median, 95th percentile and 99 percentile. The mean age of eruption of lower first molar is 6.0 years (5.8yr,6.2yr) at 95%CI and for lower canine is 10.2 years (10.0yr,l0.3yr) at 95%CI. The median age of eruption of each tooth was earlier in girls than in boys. Although the range of years during which the teeth erupted was similar in both sexes, the sequence of the individual teeth differed. All mandibular teeth, with the exception of first and second premolars in both males and females, tended to erupt earlier than their maxillary counterparts. The findings seem to correspond to earlier studies done in the other parts of the world, however the eruption time seems to be earlier compared to studies done in Thailand and Madras.